2016
DOI: 10.1007/978-3-662-53357-4_13
|View full text |Cite
|
Sign up to set email alerts
|

On the Possibility of Non-interactive E-Voting in the Public-Key Setting

Abstract: Abstract. In 2010 Hao, Ryan and Zielinski proposed a simple decentralized evoting protocol that only requires 2 rounds of communication. Thus, for k elections their protocol needs 2k rounds of communication.Observing that the first round of their protocol is aimed to establish the publickeys of the voters, we propose an extension of the protocol as a non-interactive e-voting scheme in the public-key setting (NIVS) in which the voters, after having published their public-keys, can use the corresponding secret-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Szepieniec and Bart [24] proposed a protocol similar to Kiayias and Yung that also provides fairness. Giustolisi et al [25] showed how to reuse the key-sharing round in Hao et al, reducing the number of rounds to one in all subsequent elections. Adding a commitment round to Hao et al, Khader et al [5] achieve fairness, and, by introducing a recovery round, they achieve robustness (Section VI-F).…”
Section: A Self-tallying Boardroom Voting Protocolsmentioning
confidence: 99%
“…Szepieniec and Bart [24] proposed a protocol similar to Kiayias and Yung that also provides fairness. Giustolisi et al [25] showed how to reuse the key-sharing round in Hao et al, reducing the number of rounds to one in all subsequent elections. Adding a commitment round to Hao et al, Khader et al [5] achieve fairness, and, by introducing a recovery round, they achieve robustness (Section VI-F).…”
Section: A Self-tallying Boardroom Voting Protocolsmentioning
confidence: 99%
“…We point out that our definition of verifiability is motivated by the guidelines of [CGK + 16]. In its formalization, our definition is similar to the ones of [GIR16], the verifiability for multi-input functional encryption of BGJS and the uniqueness of tally of Bernhard et al [BCG + 15]. Anyhow, the latter is formulated to hold only against computationally bounded adversaries and both BGJS16 and Bernhard et al do not take into account our condition (2) for verifiability.…”
Section: Related Workmentioning
confidence: 99%
“…In such decentralised schemes, the election is an interactive protocol between the voters only and it can even be made oneround, i.e. non-interactive, in a public key setting [7]. Whether a centralised or decentralised protocol is better-suited to a given situation depends on practical and context-specific concerns such as whether the trusted authority assumption makes sense.…”
Section: Introductionmentioning
confidence: 99%
“…However this does not guarantee that there are no fallouts in the recovery round. In [7] it was shown that using a bilinear group setting and assuming a public key infrastructure, the voting protocol can be made noninteractive, i.e. one-round.…”
Section: Introductionmentioning
confidence: 99%